Pengaruh Profitabilitas, Kepemilikan Institusional, Ukuran Perusahaan, dan Reputasi KAP Terhadap Ketepatan Waktu Pelaporan Keuangan - Dian Santika; Cahyani Nuswandari (Ekonomis: Journal of Economics and Business, 2021)
The purpose of this research is to examine and analyze the effect of profitability (ROA), institutional ownership (own), firm size (size), and auditor’s repurtation (kap) on the timeliness of financial reporting at manufacture firms listed in Indonesia Stock Exchange (BEI) period 2017-2019. In this research, the sampling technique use purposive sampling. Sample of this research is 494 data from 519 manufacture firms sector listed and sent the report on finance in BEI period 2017-2019. Technique of analysis for examining is logistic regression. The result of this reseach is the profitability and firm size positive affect on the timeliness of financial reporting, while institutional ownership and auditor’s repurtation are not significant on the timeliness of financial reporting.